Pelatihan Pengenalan Sains Sederhana Bagi Guru TK Islam Insan Cendekia Surabaya - Herawati, Andry; Listyawati, Liling; Kamariyah, Sri (Jurnal Loyalitas Sosial: Journal of Community Service in Humanities and Social Sciences, 2019)
The Islamic Kindergarten Insan Scholar aims to prepare their students for a better level of basic education based on Islamic teachings. The results of the situation analysis showed that the partners wanted to increase the performance of the teachers during the introduction to basic science for their students, which was not only theoretical or theoretical, but this is limited by the resources of teachers who do not have the capacity to provide real science learning practices that are true, and the unavailability of equipment and materials to support the learning of simple scientific practices. The Community Empowerment Program is designed to increase teachers' knowledge in the process of teaching and learning simple science practices by providing training,  and the identification and purchase of equipment and materials that support the teaching of simple scientific practices. The results of activities under the Community Empowerment Program can increase teachers' ability to learn simple scientific practices, and there are a number of tools and materials used in learning simple scientific practices for students of Islamic Kindergarten Insan Scholar. The results of the community empowerment program should be well implemented by the partners, so that TK has a competitive advantage in the future, and should foster creativity and critical thinking, which will be very beneficial for updating and preparing students to cope with their larger and more complex roles in the future.